KINETIC ISOTOPE EFFECT DURING REDUCTION OF IRON FROM A SILICATE MELT - Cohen B.A.; Levasseur S.; Zanda B.; Hewins R.H.; Halliday A.N. (My University, 2006)
Iron isotopic compositions measured in chondrules from various chondrites vary between ?57Fe/54Fe = +0.9? and -2.0?, a larger range than for igneous rocks. Whether these compositions were inherited from chondrule precursors, resulted from the chondrule-forming process itself or were produced by later parent body alteration is as yet unclear. Since iron metal is a common phase in some chondrules, it is important to explore a possible link between the metal formation process and the observed iron isotope mass fractionation. In this experimental study we have heated a fayalite-rich composition under reducing conditions for heating times ranging from 2 min to 6 h. We performed chemical and iron isotope analyses of the product phases, iron metal and silicate glass. We demonstrated a lack of evaporation of Fe from the silicate melt in similar isothermal experiments performed under non-reducing conditions. Therefore, the measured isotopic mass fractionation in the glass, ranging between -0.32? and +3.0?, is attributed to the reduction process. It is explained by the faster transport of lighter iron isotopes to the surface where reduction occurs, and is analogous to kinetic isotope fractionation observed in diffusion couples [Richter, F.M., Davis, A.M., Depaolo, D.J., Watson, E.B., 2003. Isotope fractionation by chemical diffusion between molten basalt and rhyolite. Geochim. Cosmochim. Acta 67, 3905-3923]. The metal phase contains 90-99.8% of the Fe in the system and lacks significant isotopic mass fractionation, with values remaining similar to that of the starting material throughout. The maximum iron isotope mass fractionation in the glass was achieved within 1 h and was followed by an isotopic exchange and re-equilibration with the metal phase (incomplete at ?6 h). This study demonstrates that reduction of silicates at high temperatures can trigger iron isotopic fractionation comparable in its bulk range to that observed in chondrules. Furthermore, if metal in Type I chondrules was formed by reduction of Fe silicate, our observed isotopic fractionations constrain chondrule formation times to approximately 60 min, consistent with previous work. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHONDRITE; CHONDRULE; IRON; ISOTOPIC COMPOSITION; ISOTOPIC FRACTIONATION; SILICATE MELT